Sosial Media Ruang Belajar: Pemanfaatan Platform Digital, Pendidikan Agama Islam di SMK Negeri 3 Jepara - Nuzul Ainal Mardiyah; Vera Safira; Ahmad Saefudin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
At this time, students open social media more often than books or other learning tools. Seeing this makes social media very suitable when used as a learning medium. Social media is a relatively new concept and has become the center of attention for many educators, teachers and parents in education. The aim of this research is to show that digital platforms can be a learning space for Islamic religious education in the current era. This research method uses a qualitative approach and a case study type. The data collection techniques that the author uses are preliminary research, observation, and documents. The results of this research are that the use of digital platforms and social media platforms for learning Islamic Religious Education makes it very easy for users and has various functions and can be useful as a means of innovative, creative and interactive learning processes for students, such as the one used at SMK Negeri 3 Jepara, namely Google Classroom, WhatsApp and Instagram, to CBT (an application made by SMK).